LPS-Inducible lncRNA TMC3-AS1 Negatively Regulates the Expression of IL-10 - Ye, Mengling; Xie, Minghong; Zhu, Jie; Wang, Chen; Zhou, Rui; Li, Xiaoqing (Frontiers in Immunology, 2020)
Long non-coding RNAs (lncRNAs) are essential regulators of the inflammatory response, especially for transcriptional regulation of inflammatory genes. It has been reported that the expression of TMC3-AS1 is increased following LPS stimulation. However, the potential function of TMC3-AS1 in immunity is largely unknown. Herein, we report a specific role for TMC3-AS1 in the regulation of inflammatory genes expression. TMC3-AS1 negatively regulates the expression of IL10 in intestinal epithelial cells and macrophages. Mechanistically, TMC3-AS1 may interact with p65 in the nucleus, preventing p65 from binding to the κB consensus site within IL10 promoter. These findings suggest that TMC3-AS1 may function as an important regulator in the innate immune response.